2011
DOI: 10.1186/1750-1172-6-32
|View full text |Cite
|
Sign up to set email alerts
|

A combination of transcriptome and methylation analyses reveals embryologically-relevant candidate genes in MRKH patients

Abstract: BackgroundThe Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is present in at least 1 out of 4,500 female live births and is the second most common cause for primary amenorrhea. It is characterized by vaginal and uterine aplasia in an XX individual with normal secondary characteristics. It has long been considered a sporadic anomaly, but familial clustering occurs. Several candidate genes have been studied although no single factor has yet been identified. Cases of discordant monozygotic twins suggest that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…Earlier studies have indicated that, potentially, hormone receptors may be dysfunctional in patients with the syndrome [2, 13]. A recent whole-genome analysis of our MRKHS patient population revealed overexpression of ESR1 and PGR in tissue from uterine rudiments [13]. A subsequent histological and immunohistochemical study revealed that the proliferative capacity of endometrium from MRKHS patients was significantly reduced [2].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Earlier studies have indicated that, potentially, hormone receptors may be dysfunctional in patients with the syndrome [2, 13]. A recent whole-genome analysis of our MRKHS patient population revealed overexpression of ESR1 and PGR in tissue from uterine rudiments [13]. A subsequent histological and immunohistochemical study revealed that the proliferative capacity of endometrium from MRKHS patients was significantly reduced [2].…”
Section: Discussionmentioning
confidence: 93%
“…Earlier studies have indicated that, potentially, hormone receptors may be dysfunctional in patients with the syndrome [2, 13]. A recent whole-genome analysis of our MRKHS patient population revealed overexpression of ESR1 and PGR in tissue from uterine rudiments [13].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…One in 4,500 women in the USA suffers from Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome, which is defined by aplasia of the Müllerian-derived portion of the vagina and of the uterus [15]. Magnetic resonance imaging (MRI) is often used to help identifying secondary anomalies related to MRKH syndrome and has become a useful tool in its preoperative diagnostics.…”
Section: Introductionmentioning
confidence: 99%